Relationship between some element levels and oxidative stress parameters in rats liver treated with hydroxyurea derivative compounds - Karagozoglu, Yusuf; Parlak, Akif Evren; Alayunt, Naci Ömer; Turkoglu, Semra; Yildirim, Isil; Karatepe, Mustafa (Suleyman Demirel University, 2019)
In this study, effects of hydroxyurea derivatives 1, 3, 4 - thiadiazole and schiff base compounds on some element levels and antioxidant enzyme activities in rat liver and on antioxidant enzyme levels that are parameters of oxidative stress were investigated. For this purpose, iron (Fe), zinc (Zn) and copper (Cu) concentrations were analyzed by using atomic absorption spectroscopy superoxide dismutase (SOD) and catalase (CAT) activities were measured by using a UV spectrophotometer. Fe, Zn and Cu concentrations in the liver of rats treated with these compounds were compared with levels of SOD and CAT statistically. As a result, the increase in the antioxidant activities of SOD and CAT metalloenzymes together with decrease in levels of Cu, Zn and Fe elements observed may suggest that the elements be bound to these enzymes. © 2019 Suleyman Demirel University. All rights reserved.
Keywords: Hydroxyurea; Liver; Oxidative stress; Rat; Some element